'A lot of people going that extra mile': professional collaboration and cross-disciplinarity in converged collecting institutions. (14th March 2016) - Robinson, Helena
Abstract : Much anticipation exists around the potential for the convergence of museums, libraries, archives and galleries to act as a catalyst for the cross-fertilisation of professional skills and roles across traditional domain boundaries. International scholarship and professional literature surrounding the virtual and physical integration of collecting institutions promises new opportunities for collaboration between previously 'siloed' disciplines, enhanced relationships between collections and greater access to the information resources surrounding them. To date, however, few empirical studies have examined actual cases of convergence to determine whether these benefits are being realised. This paper begins to address this lack, presenting the findings of research conducted at five converged collecting institutions located in Australia and New Zealand. Using thematic content analysis of interview data, I examine the nature of professional collaboration between library, archive, museum and gallery workers and consider the impact of role diversification on provision of museum services.